If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2x^1)+(2x^3)+(1x^3)=2(2)+(6)+(3)=
We move all terms to the left:
2(2x^1)+(2x^3)+(1x^3)-(2(2)+(6)+(3))=0
We do not support expression: x^1
| 6x+9-17x-4=-26 | | 3(x+6)^2=29 | | 0.6y=4.5 | | 3x+2+×-4=90 | | 8(a+1)=14+7a | | 1+2w+3w+4=5 | | 27+2x5=8,6 | | -14+12+1x=-12 | | 32+3m=-8(1-6m)-5m | | 10(x+4)=8x-(x | | 4+m.8=3.4 | | ⅗(x-6)=15 | | 3x+6+12x-24=180 | | 5/3r+4/3=-8/8 | | x/4+2=2x-12 | | 39-4n=-3(n+7) | | |6x+12|=6 | | x+13=-56 | | -11-3=44-2x | | (x)/(3)=5 | | 135,600,000-x=260,000,000 | | 2/3(x-12)=x+18 | | 3(12x+10)=36x-6 | | -5(x+-2)=21 | | 2x+6x−4=12 | | 5+2x=8.5 | | -5(x+-2)=22 | | 6+2x=9.5 | | −10y/11y−4+2=4/11y−4 | | 2^(2x+1)=10 | | .0.4(2-x)=0.2(x+7) | | 7x=90x+180 |